Intramuscular salbutamol in treatment of acute exacerbations of childhood asthma. Issue 7 (July 1977) - Thompson, P; Friedman, M
Abstract : Salbutamol was given by the intramuscular route to children aged 3 to 16 years with an attack of asthma. Results with a dose of 8 microgram/kg were favourable but suggested that a higher dose might be more so. 16 children thereafter were treated with 20 microgram/kg which produced a greater mean increase in peak expiratory flow rates (PEFR) without increase in side effects. This dose was then used in a double-blind crossover trial of salbutamol against a saline placebo. Half of 36 children treated with 20 microgram/kg showed rapid clinical improvement, the maximum rise in PEFR occurring within the first 5 minutes. A rise in pulse rate and occasionally a tremor were the only side effects noted. We conclude that intramuscular salbutamol 20 microgram/kg is a safe and useful initial medication in the management of the asthmatic child suffering an acute exacerbation.